EVALUATION OF BMI RELATIONSHIP WITH INCREASED D-DIMER IN COVID-19 PATIENTS AT A JAKARTA PRIVATE HOSPITAL - VESSELALDO, MANUEL; RAMATILLAH, DIANA LAILA (International Journal of Applied Pharmaceutics, 2022)
Objective: Evaluate BMI against increased D-Dimer in Covid-19 patients at one of the private hospitals in Jakarta. Methods: This study is a retrospective cohort study, and this study only covers COVID-19 patients admitted to a private hospital in the Plumpang area, North Jakarta, Indonesia, from January until July 2021. Results: The correlation between BMI and D-Dimer of COVID-19 patients using the Mann-Whitney method showed that only ten patients had higher D-Dimer 500 ng/ml, and most patients had lower D-Dimer 500 ng/ml (90%). The survival analysis for COVID-19 patients using the Kaplan Meier method showed that patients receiving normal BMI had an average survival rate of around 64% after about 17 d of treatment. Conclusion: There is the correlation between BMI with D-Dimer of COVID-19 patients.